2010
DOI: 10.1093/gerona/glq148
|View full text |Cite
|
Sign up to set email alerts
|

Premature Centromere Division of Metaphase Chromosomes in Peripheral Blood Lymphocytes of Alzheimer's Disease Patients: Relation to Gender and Age

Abstract: Chromosomal alterations are a feature of both aging and Alzheimer's disease (AD). This study examined if premature centromere division (PCD), a chromosomal instability indicator increased in AD, is correlated with aging or, instead, represents a de novo chromosomal alteration due to accelerating aging in AD. PCD in peripheral blood lymphocytes was determined in sporadic AD patients and gender and age-matched unaffected controls. Metaphase nuclei were analyzed for chromosomes showing PCD, X chromosomes with PCD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…11 Indeed, AD patients, including those with FAD mutant APP or PS and those with sporadic disease develop up to 30% aneuploid cells both in brain and peripheral tissues, indicating the presence of widespread chromosome partitioning defects in AD. [12][13][14][15][16][17][18][19][20][21] Furthermore, premature centromere division, a mitotic defect associated with chromosome mis-segregation is increased in AD 12,22,23 A causative rather than merely correlative link between aneuploidy and AD pathogenesis is supported by the facts that (1) members of families with inherited AD have an increased risk of giving birth to a Down syndrome child 10,24,25 and (2) young mothers of Down syndrome children are generally prone to chromosome mis-segregation and have a five-fold increase that they will develop AD later in life. 26,27 Recently we demonstrated that AD transgenic mouse models (which produce increased levels of Aβ 1-42) develop up to 25% aneuploid cells in both the brain and peripheral tissues, and that tissue culture cells transiently expressing FAD-mutant PS or APP or exposed to Aβ become similarly highly aneuploid within 48 hours.…”
Section: Alzheimer Aβ Disrupts the Mitotic Spindle And Directly Inhibmentioning
confidence: 99%
“…11 Indeed, AD patients, including those with FAD mutant APP or PS and those with sporadic disease develop up to 30% aneuploid cells both in brain and peripheral tissues, indicating the presence of widespread chromosome partitioning defects in AD. [12][13][14][15][16][17][18][19][20][21] Furthermore, premature centromere division, a mitotic defect associated with chromosome mis-segregation is increased in AD 12,22,23 A causative rather than merely correlative link between aneuploidy and AD pathogenesis is supported by the facts that (1) members of families with inherited AD have an increased risk of giving birth to a Down syndrome child 10,24,25 and (2) young mothers of Down syndrome children are generally prone to chromosome mis-segregation and have a five-fold increase that they will develop AD later in life. 26,27 Recently we demonstrated that AD transgenic mouse models (which produce increased levels of Aβ 1-42) develop up to 25% aneuploid cells in both the brain and peripheral tissues, and that tissue culture cells transiently expressing FAD-mutant PS or APP or exposed to Aβ become similarly highly aneuploid within 48 hours.…”
Section: Alzheimer Aβ Disrupts the Mitotic Spindle And Directly Inhibmentioning
confidence: 99%
“…CIN occurs when processes that maintain chromosome integrity and regulate chromosome segregation are disrupted [1]. In Alzheimer's disease, some features of chromosome instability have been shown in the cells of the nervous system [2,3,4,5], but also in cells of peripheral tissues [6,7,8,9]. Aneuploidy as a form of chromosome instability is a relevant factor in neurodegenerative changes in AD and in ageing [2,8,10,11,12,13] with reports that the number of aneuploid neurons in affected brain regions exceed 20% [14].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon shows that deregulation of the time of centromere separation can be considered as a manifestation of CIN leading to aneuploidy [19,22,23,24]. Moreover, our previous data suggests that PCD is a distinctive feature of AD, rather than an epiphenomenon of chronological ageing [7]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in the frequency of SA has been reported with cigarette and bidi smokers and increased cytogenetic damage has been observed in peripheral blood lymphocytes and exfoliated buccal mucosa cells to pan masala (Farred et al, 2011). On the contrary, Zivkovic et al (2010) have reported a significant decrease in frequency of SA between Alzheimer disease (AD) patients and controls which could be related to etiology or pathology of genome instability in AD. In the present study, we found higher frequency of SA with combined in vitro treatments of 5-FU and cisplatin in comparison to non-treated oral squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 98%